2020
DOI: 10.1242/dev.184762
|View full text |Cite
|
Sign up to set email alerts
|

VAPYRIN-like is required for development of the moss Physcomitrella patens

Abstract: The VAPYRIN (VPY) gene in Medicago truncatula and Petunia hybrida is required for arbuscular mycorrhizal (AM) symbiosis. The moss Physcomitrella patens has a close homologue (VPY-like, VPYL), although it does not form AM. Here, we explore the phylogeny of VPY and VPYL in land plants, and we study the expression and developmental function of VPYL in P. patens. We show that PpVPYL is expressed primarily in the protonema, the early filamentous stage of moss development, and later in rhizoids arising from the leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…We observed abnormal positioning of branching cells in the cornichon mutants (Figure 2A-B and Supplemental Figure S4). Until now, it has only been reported that mutants in Myosin VIII (Wu et al, 2011) and a Vapyrin-like (VPY-like) protein (Rathgeb et al, 2020) exhibit these branching defects. In moss protonemata, one of this cornichon-interacting proteins could be a VPY-like protein according to its localization to puncta in the cytoplasm and around the nucleus, coincident to that we observed for CNIH2 (Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed abnormal positioning of branching cells in the cornichon mutants (Figure 2A-B and Supplemental Figure S4). Until now, it has only been reported that mutants in Myosin VIII (Wu et al, 2011) and a Vapyrin-like (VPY-like) protein (Rathgeb et al, 2020) exhibit these branching defects. In moss protonemata, one of this cornichon-interacting proteins could be a VPY-like protein according to its localization to puncta in the cytoplasm and around the nucleus, coincident to that we observed for CNIH2 (Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…In moss protonemata, one of this cornichon-interacting proteins could be a VPY-like protein according to its localization to puncta in the cytoplasm and around the nucleus, coincident to that we observed for CNIH2 (Figure 5A). The localization of VPY and VPY-like proteins was denoted as vapyrin bodies related to the TGN and endosomes, but also associated with the endoplasmic reticulum (Pumplin et al, 2010; Feddermann et al, 2010; Liu et al, 2019; Bapaume et al, 2019; Rathgeb et al, 2020). Although the function of Vapyrin (VPY) and VPY-like proteins is unknown, they are only found in plants and possess a vesicle-associated protein (VAP) domain at their N-terminus, and several ankyrin repeat domains at the C-terminus, with both domains predicted to be involved in protein-protein interactions (Pumplin et al, 2010; Feddermann et al, 2010), opening the possibility that they could associate with CNIH2.…”
Section: Discussionmentioning
confidence: 99%
“…This is illustrated by VAPYRIN and VPY-like, two genes originating from an embryophyte-specific gene duplication. In angiosperm both genes are co-eliminated with the loss of AM symbiosis while they are, one or the other, maintained in Bryophytes irrespective of their symbiotic abilities (57,65). In the moss P. patens, inactivation of VPY-like, the paralog maintained in mosses, results in developmental defects in the gametophyte (65).…”
Section: Symbiotic Gene Co-elimination Differs Between Bryophytes and Tracheophytes And Maymentioning
confidence: 99%
“…Additionally, evidence that P. patens has (or had) the capacity for interacting with fungi can be supported by the presence of orthologs essential to detecting and forming plant–fungal interaction. Some conserved genes that are indicative of this possibility include a chitin‐like receptor PpCERK1 necessary to signal the environmental presence of fungi, a VAPYRIN ‐like homolog with only known function in forming symbiotic interaction between plants and fungi, and functional strigolactone hormone pathways with secondary functions known to signal host root proximity to symbiotic and parasitic fungi (Bressendorff et al., 2016; Delaux & Schornack, 2021; Proust et al., 2011; Rathgeb et al., 2020).…”
Section: Introductionmentioning
confidence: 99%